(untitled) (Malaysian Journal of Civil Engineering, 2018)
Construction projects require proper knowledge sharing implementation in order to satisfy the demand of today’s knowledgeable and aggressive clients. The effective knowledge sharing process in construction projects is certainly one of the key components to success. It is crucial for the construction industry to develop a new strategy in order to align with the other industries especially in the knowledge sharing aspect. The primary aim for this paper is to determine factors that contribute to barriers for knowledge sharing implementation in Malaysian construction organisation. This study also identify solutions that construction organisation should adapt strategies towards achieving proper knowledge sharing implementation. The factors identification process was collected through intensive literature study and supported by 2 numbers of interview sessions conducted in contractor organisation. 90 sets of questionnaire were distributed in determining the barriers and solutions. As the results, the factor of intangible benefit contributed to the barriers. Furthermore, role model in organisation is among solutions for Malaysian contractor organisation in order to promote knowledge sharing initiative in the industry. The output of this study is recommended for a milestone of knowledge sharing studies in Malaysia particularly to construction industry to transform in knowledge era in the new globalised world.